Mechanical properties of polyamide 12 fabricated by selective laser sintering and multi jet fusion - Ng, Qinxuan (Nanyang Technological University, 2020)
Additive manufacturing (AM) has been evolving from a technique of rapid prototyping to an indispensable rapid manufacturing method for producing end-use parts. Among the various subclass of AM processes, powder bed fusion (PBF) holds great potential for small to medium batch production, due to its advantages of elimination of the supporting structures, good and consistent mechanical properties compared with conventional manufacturing processes, etc. As far as polymer materials are concerned, selective laser sintering (SLS) and the lately developed multi jet fusion (MJF) are two typical PBF AM processes. SLS has been a well-established and widely studied process, however, the investigation into the MJF process is lacking. This research aims to evaluate the uniaxial tensile and fatigue properties of the polyamide 12 (PA12) parts printed by SLS and MJF. The effects of different building orientations on the surface topography, tensile and fatigue properties and failure mechanism of the specimens produced by each process were examined. The results show that the MJF-printed specimens reveal a smaller value of surface roughness than the SLS specimens regardless of the building orientation. Both the MJF-printed and SLS-printed PA12 specimens show anisotropic tensile properties in the XY and Z orientations. For SLS, the specimens built in XY orientation was the highest in ultimate tensile strength (UTS), Young’s modulus and elongation at break; while for MJF, the specimens built in Z orientation is the best. Overall, the MJF-printed specimens show to be brittle than the SLS-printed specimens but have slightly higher UTS of 51 MPa in Z orientation. The SLS-printed specimens in XY orientation show higher numbers of cycle to failure than that built in Z orientation at a relatively high stress level (> 30 MPa), but the disparity became marginal when low stresses were applied. The building direction has a little significant effect on the fatigue performance of the MJF-printed specimens. Both the SLS-printed and the MJF-printed specimens have an endurance limit of about 24 MPa as shown in the S-N curves. The tensile fractography analysis shows that the MJF-printed specimens in Z orientation had a better interlayer fusion of particle than SLS. Besides, both the MJF-printed and the SLS-printed specimens show a similar fracture mechanism where crack initiates from unmelted powder particles, propagation though craze and form tearing edges. From the fatigue fractography, the area with unmelt powder particles acted as the stress concentrator and the origin of the fatigue cracks. It was also found that the MJF-printed specimens in Z orientation show a wave-like structure, indicating the good powder fusion in individual layers.